OIL PALM AND POVERTY IN KETAPANG REGENCY - B6111038, ENDANG SULISTIORINI (Jurnal Ekonomi Daerah (JEDA), 2016)
This Thesis entiled "Oil Palm and Poverty in Ketapang Regency" is a descriptive research, an aims to test and analyze the effect of the expansion of agricultural lands and the amount of palm oil production on poverty in Ketapang Regency. The variables studied were the number of poor families, the land area (plantation) and the number of palm oil production. The method of analysis is a multiple regression with panel data in 14 districts during six years 2010 to 2015. The data of poor families sourced from the Regional Secretariat of the Ketapang District from base of the Target Families Social Direct Protection Prorgam (PPLS) in year 2008, 2011 and 2012-2015, that taken from 14 districts, the data land area (plantation) and the number of farm production was taken from reports plantation Office of Ketapang regency in relevant period. The results of the analysis of (partial) t-test) shows that there is a negative and significant impact on the land (plantation area) and the number of farm production was positive effect but not significant of palm oil production on poverty in Ketapang. The test results simultaneously (together) the two variables showed (plantation are and number of product) was a significant effect with high F value because the probability is low. The relationship of all the variables indicated by the coefficient of determination R2 amounted to 0,9788. This means that the influence of these two variables (land area and total production) against poverty was 97.88%, while the rest (2.12%) influenced by other factors. Keywords : Poor Family, Oil Palm Plantations, The Land Area, The Number of Production